Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1976
DOI: 10.1099/00207713-26-4-474
|View full text |Cite
|
Sign up to set email alerts
|

Synonymy of Mycobacterium simiae Karasseva et al. 1965 and Mycobacterium habana Valdivia et al. 1971

Abstract: On the basis of their physiological and biochemical properties and their antigenic structures, as revealed by gel diffusion systems, Mycobacterium simiae Karasseva et al. 1965 and Mycobacterium habana Valdivia et al. 1971 are regarded as belonging to the same'species. The correct name of this species, i.e. , the legitimate name which has priority, is M . simiae. M . habana is thus a later subjective synonym of M . simiae. Karasseva et al. (6) investigated spontaneous mycobacterial infections of monkeys and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 1 publication
0
14
0
Order By: Relevance
“…M. simiae isolates grow over the pH range 5.5 to 7.5 (400). M. simiae produces niacin, unlike other nontuberculous mycobacteria, and has urease but lacks phosphatase and nitrate reductase activities (541). The pattern of cell-free antigens of M. simiae is unique, although approximately half are shared with members of the M. avium complex (540).…”
Section: Characteristics Of M Simiaementioning
confidence: 99%
See 2 more Smart Citations
“…M. simiae isolates grow over the pH range 5.5 to 7.5 (400). M. simiae produces niacin, unlike other nontuberculous mycobacteria, and has urease but lacks phosphatase and nitrate reductase activities (541). The pattern of cell-free antigens of M. simiae is unique, although approximately half are shared with members of the M. avium complex (540).…”
Section: Characteristics Of M Simiaementioning
confidence: 99%
“…The pattern of cell-free antigens of M. simiae is unique, although approximately half are shared with members of the M. avium complex (540). There appear to be two serotypes represented among the M. simiae strains collected and serotyped to date (541). M. simiae and Mycobacterium habana are synonymous (358,490,541).…”
Section: Characteristics Of M Simiaementioning
confidence: 99%
See 1 more Smart Citation
“…Although the synonymy between M. simiae and 'M. habana' has been clearly demonstrated (Weiszfeiler & Karczag, 1976), the epithet 'habana' is maintained for the original collection of strains, in particular because a series of investigations has suggested a vaccine potential for strain 'M. habana' TMC 5135 in tuberculosis and leprosy (reviewed by Mederos et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In 1975, WEISZFEILER and KARCZAG [2] found that the previously described species M. habana was in reality also M. simiae.…”
mentioning
confidence: 99%